O relações-públicas como agente na inclusão de pessoas LGBT+ em organizações - Porto, Murilo Augusto da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Life in society, basically, is developed by the relationships between people, which have individual characteristics and aspects. Such relationships generate both harmony and conflict between individuals and organizations, which are formed by them, and must understand how it influences their existence and performance. This paper discusses the issue of diversity within organizations, more specifically about adversities related to the LGBT + community. The main objective is to reflect on the importance of the Public Relations professional in the mediation and minimization of conflicts between organizations and their publics, especially in the issue of the marginalization of the LGBT + social minority and awareness of the importance of diversity to the organizational culture of an organization. The methodology used in the development of the study was the bibliographical review of authors such as Kunsch (2003), Green (2000), Marchiori (2005, 2008), Louro (2009) and Grunig Equal, promoted by the Office of the United Nations High Commissioner for Human Rights (OHCHR). In this way, the LGBT + community panorama and the context of the organizations, through the communication bias, were raised so that it was possible to identify the issue related to diversity.

A vida em sociedade é, basicamente, desenvolvida pelas relações entre os indivíduos, os quais têm características e aspectos individuais. Tais relações geram tanto harmonia, quanto conflito entre os indivíduos e as organizações, as quais são formadas por eles e precisam compreender como isso influencia em sua existência e atuação. Este trabalho discute a questão da diversidade no âmbito das organizações, mais especificamente sobre adversidades relacionadas à comunidade LGBT+. O objetivo principal é refletir sobre a importância das atividades do relações-públicas na mediação e gestão de conflitos entre organizações e seus públicos, principalmente na questão da marginalização da minoria social LGBT+ e conscientização da importância da diversidade para a cultura organizacional de uma organização. A metodologia utilizada no desenvolvimento do estudo foi a revisão bibliográfica de autores como Kunsch (2003), Green (2000), Marchiori (2005, 2008), Louro (2009), Grunig (2009), assim como a análise da campanha ONU Livres & Iguais, promovida pelo Escritório do Alto Comissariado das Nações Unidas para os Direitos Humanos (ACNUDH). Deste modo, foram levantados o panorama da comunidade LGBT+ e o contexto das organizações, pelo viés da comunicação, para que fosse possível identificar a problemática ligada à diversidade.
Keywords: Pessoas LGBT; Comunicação; Relações públicas; Communication